Tear osmolarity and tear film parameters in patients with ocular rosacea in response - Karaman Erdur, Sevil (Lippincott Williams & Wilkins, 2016)
We found the opportunity to read the article by Karaman Erdur et al.1 entitled “Tear Osmolarity and Tear Film Parameters in Patients With Ocular Rosacea.” They evaluated 25 eyes of 25 patients with ocular rosacea, 25 eyes of 25 patients with rosacea without ocular involvement, and 20 eyes of 20 healthy individuals using the Ocular Surface Disease Index (OSDI) questionnaire, Schirmer I test, tear film break-up time (T-BUT), scoring of ocular surface fluorescein staining using modified Oxford scale, and tear osmolarity. They found that tear osmolarity values, OSDI, and Oxford scale scores were significantly higher and Schirmer 1 and T-BUT were lower in ocular rosacea group than the others. They concluded that further studies inspecting meibomian gland dysfunction in rosacea patients are needed.
WOS: 000387490000014
Keywords: Dry Eye; Ocular Surface; Meibomian Gland Dysfunction; Tear Osmolarity; Ocular Rosacea